A Web-Based Navigation Control System for Lake Toba Cleaning Using NodeMCU ESP8266 and Pulse Width Modulation (PWM) - Simatupang, Frengki; Manalu, Istas Pratomo; Siagian, Pandapotan; Sigiro, Marojahan Mula Timbul; Wowiling, Gerry Italiano; Sinambela, Eka Stephani; Saragih, Ripandy; Yosheva, Grace; Silaen, Romaito (Program Studi Teknik Mesin Universitas Pamulang, 2025)
Waste pollution in Lake Toba has become a critical environmental issue, threatening both its natural beauty and ecological sustainability. Manual waste collection methods remain limited in terms of efficiency and operational reach. This study aims to design and evaluate a web-based navigation control system for a floating surface-cleaning device utilizing the NodeMCU ESP8266 microcontroller. The system enables real-time control of direction and motor speed through a web interface, employing Pulse Width Modulation (PWM) for precise speed regulation. A prototype-based engineering approach was adopted, encompassing system design, implementation, and performance testing on land and in water environments. The experimental results indicate that the system successfully responded to all navigation commands (forward, backward, turn, pivot, and stop) with 100% accuracy under a stable local Wi-Fi network. Motor performance in water was found to be approximately 15–20% lower than on land due to fluid resistance. Battery endurance tests showed an operational time of approximately 3 hours on land and 2.1 hours in water at a 60% PWM duty cycle. Overall, the system demonstrates effective and flexible performance and holds promise for further development through the integration of sensors, camera modules, GPS-based autonomous navigation, and LoRa communication.